USE OF THE PAVLIK NAIL FOR FEMORAL SHORTENING - Pach, Miroslav; Uvizl, Miroslav; Holibka, Radomir (Biomedical papers, 2006)
Background: Selecting the correct type of osteosynthesis has a crucial impact on the final outcome of shortening operations for leg length discrepancy (LLD). One approach, introduced at the beginning of the 1950's, was fixation of femoral shortening osteotomy using the Pavlik intramedullary nail.Aim: The aim of this paper is to draw attention to the outstanding contribution of this great representative of Czech orthopaedics, to compare his method with other approaches to osteosynthesis, and, in the original patient set, to evaluate the long-term results of femoral shortening based on available medical records.Material and methods: Of 34 operated patients, a subset of 11 underwent femoral shortening and fixation by the Pavlik nail and were evaluated according to the Merle d'Aubigne and Postel score. Preoperative, postoperative and current radiographs are described.Results: The results were: excellent (6), good (3), and fair (2). There was no infection, thrombembolism, or osteosynthesis failure. Heterotopic ossification was recorded. The general validity of Pavlik's technical orthopaedic thinking is confirmed by stable osteosynthesis, and prevalence of excellent and good results.Conclusion: This study has confirmed the general validity of Pavlik's technical and orthopaedic thinking. His intramedullary nail was a suitable instrument for achieving stable osteosynthesis after a shortening femoral osteotomy. There was neither nail migration nor bone fragment dislocation. No additional plaster immobilization was used and this promoted early, progressive and rapid rehabilitation oriented towards active exercises. The low complication rate was evidence of correct methodology. Despite the undoubted value of the Pavlik femoral intramedullary nail, this method has never become widespread.
Keywords: Keywords: Leg length discrepancy (LLD)/Femoral shortening/Osteosynthesis/Pavlik nail/ Long-term results/Merle d'Aubigne